Short-term exposure to exogenous lipids in premature infants and long-term changes in aortic and cardiac function - Lewandowski, A; Lazdam, M; Davis, E; Kylintireas, I; Diesch, J; Francis, J; Neubauer, S; Singhal, A; Lucas, A; Kelly, B; Leeson, P (2011)
Objective-: Intravenous lipid use is associated with an acute hyperlipidemia, but long-term consequences have not been studied. We investigated whether elevated lipids in humans during the critical period of preterm neonatal life have a long-term impact on aortic and myocardial function relevant to adult disease. Methods and results-: We followed up 102 subjects born prematurely and now aged 23 to 28 years. Eighteen received intravenous lipids as neonates and were matched to controls with equivalent perinatal characteristics. Global and regional aortic stiffness and left ventricular function were assessed by cardiovascular magnetic resonance. Those who received intravenous lipids had greater aortic stiffness in early adulthood (P=0.0002), with greater stiffness in the abdominal aorta (P=0.012). The relationship was graded according to the elevation in neonatal cholesterol induced by intravenous lipids (P<0.0001) but not other metabolic parameters altered by the infusion. Peak systolic circumferential strain was also reduced in the lipid group (P=0.006), which, again, was proportional to neonatal cholesterol level (P<0.01). Conclusion-: Aortic and myocardial function in young adulthood is associated with intralipid exposure during neonatal life for preterm infants, in a graded manner related to the rise in cholesterol. Circulating cholesterol during critical developmental periods may have long-term impacts on the human cardiovascular system. © 2011 American Heart Association. All rights reserved.